THE RELATIONSHIP OF COMMUNITY PERCEPTION WITH COVID-19 VACCINE PARTICIPATION AT THE PUBLIC HEALTH CENTER: HUBUNGAN PERSEPSI MASYARAKAT DENGAN PARTISIPASI VAKSINASI COVID-19 DI PUSKESMAS - Rahmadani, Suci; Nurdiana; Palutturi, Sukri; Nazaruddin, Balqis (Universitas Islam Negeri Alauddin Makassar, 2026)
Background: The emergence of COVID-19 in early 2020 caused high mortality worldwide. The government expects public participation in carrying out vaccines to end the pandemic. The low level of community participation is influenced by people's perceptions of getting the COVID-19 vaccine. This study examines the relationship between perceptions and community participation in the Public Health Center's COVID-19 vaccination program. Method: This study used a quantitative survey with a cross-sectional design. The study is conducted at Rappokalling Health Center, Makassar City, Indonesia. The samples obtained were 269 respondents in each village in the working area of the Public Health Center using the proportionate stratified random sampling technique. Data analysis used the Chi-Square test. Result: The results showed that perceived benefits (P = 0.001) and perceived barriers (P = 0.000) had a relationship with community participation in implementing the COVID-19 vaccination at the Public Health Center. Perceived susceptibility (P = 0.548), perceived severity (P = 0.155), and cues to act (P = 1,000) had no relationship with community participation in implementing the COVID-19 vaccination at the Public Health Center. Conclusion: It can be concluded that perceived benefits and perceived barriers have a relationship with community participation in carrying out the COVID-19 vaccination, while perceptions of vulnerability, seriousness, and cues to act have no relationship with community participation in carrying out the COVID-19 vaccination.